Evaluation of electrochemical performance of solid-oxide fuel cell anode with pillar-based electrolyte structures. (3rd May 2019) - Shimura, Takaaki; Nagato, Keisuke; Shikazono, Naoki
Abstract: Among the gas, ion, and electron diffusion processes in solid-oxide fuel cell (SOFC) electrodes, it is generally known that ionic conduction has the most impact on their electrochemical performance. Therefore, enhancement of the effective ionic conductivity of electrodes is a useful approach to reduce the overpotential. Yttria-stabilized zirconia (YSZ) pillars can be effective solutions to enhance the effective ionic conductivity of SOFC anodes. In this study, the influence of YSZ pillar structures on the electrochemical performance of SOFC anodes was evaluated by numerical simulation and experiments. First, to reveal the electrochemical reaction kinetics of anodes with pillar structures, a three-dimensional electrochemical simulation was conducted by the lattice Boltzmann method. The microstructure without pillars obtained by a focused ion beam scanning electron microscopy (FIB-SEM) measurement was used as the reference structure. Then, the original structure was replaced with YSZ phase to obtain virtual microstructures with YSZ pillars. With YSZ pillars, predicted area specific resistance became smaller than that of the reference structure, in spite of decrease in percolated TPB density. The electrochemical potential distribution of oxide ion and charge-transfer currents clearly show increase in the effective ionic conductivity. Relationships between overpotential and pillar geometries were parametrically discussed. Then, electrochemical performance of Ni-YSZ anode with the YSZ pillar structure formed by modifying the YSZ electrolyte surface was evaluated. By sputtering Ni-YSZ on pillar structures, stable electrochemical performance was obtained. Graphical abstract: Image 1 Highlights: Influence of YSZ pillar structures on Ni-YSZ anode performance was investigated. 3D electrochemical simulations were conducted by lattice Boltzmann method. Performance enhancement is achieved by enlarged effective ionic conductivity. Anodes with pillar structures were fabricated by laser ablation and tested.